Answer:
x = -2
Step-by-step explanation:
[tex] 3x^2+12x+12=0 [/tex]
First, try to factor out a common factor from every term.
The coefficients are 3, 12, and 12.
The GCF (greatest common factor) of 3, 12, and 12 is 3, so factor out a 3 from all terms.
[tex] 3(x^2+4x+4)=0 [/tex]
Now divide both sides by 3.
[tex] x^2+4x+4=0 [/tex]
You have a quadratic trinomial of the form x^2 + ax + b.
To factor it, you need to find two numbers that multiply to b and add to a. Call these two numbers p and q.
Then the factorization is (x + p)(x + q).
In your case, you have
[tex] x^2 + 4x + 4 = 0 [/tex]
In this case, a = 4 and b = 4.
You need two numbers that multiply to 4 and add to 4.
The numbers are 2 and 2.
Then the factorization is
[tex] (x + 2)(x + 2) = 0 [/tex]
Now set each factor equal to zero and solve for x.
x + 2 = 0 or x + 2 = 0
x = -2 or x = -2
Answer: x = -2